Highly Efficient Oxidative Cyanation of Aldehydes to Nitriles over Se, S, N‐tri‐Doped Hierarchically Porous Carbon Nanosheets. Issue 39 (20th August 2021) - Hua, Manli; Song, Jinliang; Huang, Xin; Liu, Huizhen; Fan, Honglei; Wang, Weitao; He, Zhenhong; Liu, Zhaotie; Han, Buxing
Abstract: Oxidative cyanation of aldehydes provides a promising strategy for the cyanide‐free synthesis of organic nitriles. Design of robust and cost‐effective catalysts is the key for this route. Herein, we designed a series of Se, S, N‐ tri ‐doped carbon nanosheets with a hierarchical porous structure (denoted as Se, S, N‐CNs‐ x, x represents the pyrolysis temperature). It was found that the obtained Se, S, N‐CNs‐ 1000 was very selective and efficient for oxidative cyanation of various aldehydes including those containing other oxidizable groups into the corresponding nitriles using ammonia as the nitrogen resource below 100 °C. Detailed investigations revealed that the excellent performance of Se, S, N‐CNs‐ 1000 originated mainly from the graphitic‐N species with lower electron density and synergistic effect between the Se, S, N, and C in the catalyst. Besides, the hierarchically porous structure could also promote the reaction. Notably, the unique feature of this metal‐free catalyst is that it tolerated other oxidizable groups, and showed no activity on further reaction of the products, thereby resulting in high selectivity. As far as we know, this is the first work for the synthesis of nitriles via oxidative cyanation of aldehydes over heterogeneous metal‐free catalysts. Abstract : Metal‐free Se, S, N‐ tri ‐doped carbon nanosheets (Se, S, N‐CNs‐ 1000 ) show high activity and selectivity for oxidative cyanation of various aldehydes to synthesize organic nitriles using ammonia as the nitrogen resource. Other oxidizable groups were tolerated, and no further reaction of the product was observed over Se, S, N‐CNs‐ 1000 .